On‐surface synthesis and atomic scale characterization of unprotected indenofluorene polymers. Issue 12 (3rd March 2022) - Di Giovannantonio, Marco; Fasel, Roman
Abstract: Polycyclic hydrocarbons with nonzero radical character have attracted enormous interest as potential active media for organic electronics and spintronics. In this context, indenofluorenes are an intriguing class of formally antiaromatic, biradical materials with a radical character that depends on the connectivity of their six‐ and five‐membered rings. Synthesis of indenofluorene polymers and related compounds, first achieved in the early '90s with the production of ladder‐type chains, represents a major step toward incorporation of these systems into devices. However, solution‐based synthetic protocols require bulky protecting groups to stabilize the most reactive sites and, at the same time, to improve solubility and processability of such compounds. The preparation of various pristine – that is, unprotected—indenofluorene polymers has recently become possible via the on‐surface synthesis approach, where the resulting nanostructures are supported and efficiently stabilized by the underlying substrate in ultrahigh vacuum conditions. Here, an overview of these recent works is given, with a focus on synthetic challenges, structural details and electronic properties. Abstract :